Sociology of Children's Worship Spaces: A Study of Prayer Rooms and Daily Piety at Lesmana 2 Public Elementary School - Muh Hanif; Afniatul Nofriah (Penerbit Hellow Pustaka, 2026)
This study aims to describe the role of the prayer room (musholla) as a place of worship and social space for students, explain the practice of daily piety through the habit of congregational prayer, and analyze the roles of teachers, schools, and families in shaping the religious character of children at SD Negeri 2 Lesmana. This study used a qualitative approach with field research. Data collection techniques were conducted through observation, interviews, and documentation of students' religious activities in the school prayer room. The results indicate that the prayer room functions not only as a place for worship but also as a space for religious habits, character education, and student social interaction. Through activities such as Duha prayer (Duha), Zuhur prayer (Dhuhr), BTQ (Recitation of the Quran), group prayer, and teacher involvement in mentoring, students learn discipline, order, responsibility, maintaining togetherness, and respecting rules. Students' daily practice of piety is formed through the habit of worship that is carried out routinely, purposefully, and sustainably. Religious character formation is strengthened when schools, teachers, and families work together to instill religious values both at school and at home.